Embryonic somite formation generated by genetic network oscillations with noise - Mazzitello, Karina Irma (2012)
In most vertebrate species, the body axis is generated bythe formation of repeated transient structures called somites. Thisspatial periodicity in somitogenesis has been related to the geneticnetwork oscillations in certain mRNAs and  their associated geneproducts in the cells forming the presomitic mesoderm. The currentmolecular view of the mechanism underlying these oscillationsinvolves negative-feedback regulation at transcriptional andtranslational levels. The spatially periodic nature of somiteformation suggests that the genetic network  involved must displayintracellular oscillations that interact with a longitudinalpositional information gradient, called determination front, downthe axis of vertebrate embryos to create this spatial patterning.Here we consider a simple model for diploid cells based on thiscurrent biological picture  considering  gene regulation  as a noisyprocess relevant in a real developmental situation and study itsconsequences for somitogenesis. Comparison is made with the known properties of somite formation in the zebrafish embryo.